A Note on the Generalized Camassa-Holm Equation. (25th December 2014) - Wu, Yun; Zhao, Ping
Abstract : We study the generalized Camassa-Holm equation which contains the Camassa-Holm (CH) equation and Novikov equation as special cases with the periodic boundary condition. We get a blow-up scenario and obtain the global existence of strong and weak solutions under suitable assumptions, respectively. Then, we construct the periodic peaked solutions and apply them to prove the ill-posedness inH s withs < 3 / 2 .